P3.153 Clinical Features and Treatment Responses in 300 Pharyngeal Chlamydia Trachomatis Infections in MSM. (13th July 2013) - Haidari, G; Stockwell, S; Elgalib, A; Surah, S; Tong, W C Y; Alexander, S; White, J A
Abstract : Background: In men who have sex with men (MSM), orogenital sexual practises and an increase in triple site testing have resulted in detection of pharyngeal Chlamydia trachomatis (CT) infections. Clinical features are not well-described and there are no evidence-based treatment guidelines for this site of infection. We describe a cohort of MSM with pharyngeal CT seen in a large urban GUM clinic. Methods: Retrospective analysis of 300 MSM with pharyngeal CT seen from 2009–2012; 31% were HIV positive, > 50% on antiretroviral therapy. Diagnosis was by CT RNA detection by Aptima Combo2 (Gen-Probe). Results: Of 300 cases, 11.6% of patients described throat symptoms. Concurrent rectal CT was seen in 53%; urethral CT in 12%; 21 patients had CT at all 3 sites. Of 133 CT-positive specimens tested for lymphogranuloma venereum (LGV) DNA, 3 were positive (2.3%); only 1/3 had severe throat symptoms. The other two had symptomatic rectal LGV. Patient: Treatment comprised ≥ 7 days doxycycline (100mg bd) for 77% or azithromycin (1g stat) for 31%. Only 68% of patients (185/272) returned for pharyngeal test of cure (TOC) at a median 48 days. There were 5 positive TOCs; however 4 of these were likely re-infections rather than treatment failure, due to high levels of ongoing sexual risk (3 had received 7 days and one 14 days doxycycline). One patient had persistent chlamydial infection and CT conjunctivitis despite having received azithromycin 1g stat 5 weeks prior. Conclusions: With the use of dual NAAT screening of throat swabs, pharyngeal CT detection will occur in 1–2% of MSM. It is a source of onward transmission and can occasionally cause throat symptoms. Both azithromycin 1g or 7+ days of doxycycline seem to be efficacious treatment, although with high rates of concurrent rectal CT infection doxycycline is preferred. An association with CT conjunctivitis needs further study.